Entropy analysis due to conjugate-buoyant flow in a right-angle trapezoidal enclosure filled with a porous medium bounded by a solid vertical wall - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Ioan (Elsevier France-Editions Scientifiques Medicales Elsevier, 2009)
Entropy generation due to buoyancy induced convection and conduction in a fight angle trapezoidal enclosure filled with fluid saturated porous medium has been performed numerically. Left vertical solid wall of the trapezoidal enclosure has a finite thickness and conductivity. The outside temperature of the solid wall is higher than that of inclined wall, while horizontal walls are adiabatic. The governing Darcy and energy equations are solved numerically using a finite difference method. The study is performed for different governing parameters including the Rayleigh number (50 <= Ra <= 1000), inclination angle of the inclined wall of the enclosure (gamma = 35 degrees, 45 degrees and 60 degrees), dimensionless thickness of the solid vertical wall (S = 0.05, 0.1 and 0.2), and thermal conductivity ratio (k = 0.1, 1.0 and 10). Entropy generation is calculated by using the obtained velocities and temperature distributions from the computer code. Results are presented for the Bejan number, local and mean Nusselt numbers, streamlines, isotherms, iso-Bejan lines and entropy generation contours. It is found that the most important parameters on heat transfer and fluid flow are thermal conductivity ratio and dimensionless thickness of the solid wall of the enclosure. Thus, these parameters also generate entropy for the whole system. It is also found that increasing the Rayleigh number decreases the Bejan number; however, heat transfer is an increasing function of Rayleigh number. (c) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Conjugate trapezoidal enclosure; Entropy generation; Porous medium; Natural convection; Numerical results